Comparación del exámen directo con el método de Willis para determinar geohelmintiasis en escolares que acuden al Hospital del Cantón Saraguro y sus factores predisponentes. - Alulima Palacios, Andrea (2013)
In Latin America, one of the most important causes of mortality in children is the set of intestinal parasites as being highly prevalent, affecting the health and well being of this age group and society. This clear impact is often masked by the diagnostic difficulties given by the non-specificity of symptoms, or low parasitic loads no clinical manifestations or difficulties for timely medical consultation of the affected part (1). Thus, in order to compare two techniques to determine STH 207 fecal samples were analyzed schoolchildren who attended outpatient Saraguro Base Hospital during the months of June-July 2012, which were analyzed, by direct examination with iodine and saline solution (2) and examining Willis concentration by flotation (3) it is based on bringing the feces in a liquid of higher density than the parasites so that these are concentrated on the surface. STH prevalence was 62% with direct examination and 77% with the technique of Willis, the highest prevalence of STH was found in the age group of 8-10 years (42%) being the most affected men, were diagnosed STH three species of Hymenolepis Nana being the most prevalent in both direct examination (30%) and Willis technique (35%). The most common risk factor was unsuitable environmental conditions in which 97% moist soil stands, poor housing conditions and lack of basic services such as drinking water. Keywords: Intestinal parasites, STH, Direct method, Method of Willis.